Efeitos do treinamento resistido e treinamento aeróbio na qualidade do sono e aptidão física na Doença de Parkinson: uma revisão sistemática - Costa, Matheus Marques Mesquita da (2024)
Sleep disturbances occur in both Parkinson's disease and aging, involving difficulties in initiating and maintaining sleep and dysfunctions in the mechanisms controlling the sleep-wake cycle. Physical exercise, as an adjunct therapy, has been shown to improve subjective sleep quality, strength, and walking ability, as well as increase sleep efficiency and total sleep time. However, the optimal exercise modality remains unclear. This systematic review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and its protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42024548401).The research was guided by the following question, formulated using the PICOS strategy (population, intervention, comparison, outcome, and survey): "What are the effects of resistance and aerobic training on improving sleep quality and physical fitness in patients with Parkinson's disease?" The databases used included PubMed, Embase, Scopus, and the Virtual Health Library (VHL). Out of 2034 initial studies, 9 were included, totaling 515 participants. The results indicate that physical exercise improves sleep quality and physical fitness, but there is a need for more detailed exercise programs. The methodological quality of the studies was assessed using the Cochrane ROB 2 tool.